Mathematics Anxiety Among High School Students: Causes, Consequences, and Coping Mechanisms - Salma E. El-Far; Ahmed M. El-Mutaz; Fathi A. Ghariani (International Journal of Mathematics and Science Education, 2024)
This research addresses mathematics anxiety among high school students, examining its causes, impacts on academic performance, and students' coping mechanisms. Through a mixed-method approach combining surveys and interviews, the study identifies key factors contributing to math anxiety, including social influences, teaching styles, and individual differences. Findings suggest that mathematics anxiety has a substantial negative effect on academic achievement, but that certain coping strategies, such as peer collaboration and guided practice, can mitigate this impact.